The intersection of infant substance exposure, foster care placement & child welfare policy - Abigail Novak; Colleen K. Gutman; Vitoria De Francisco Lopes; Brian B. Boutwell (Child Protection and Practice, 2025)
Fetal exposure laws mandate child welfare system referral for infants exposed to substances. Though these laws are relatively common, examinations of the consequences of child welfare system involvement for infants exposed to substances are less frequent. The purpose of this paper was to examine the impact of out-of-home placement at 18 and 36 months for substance-exposed infants. Using the National Survey of Child and Adolescent Well-being II (NSCAWII)'s sample of infants (<1 year) referred to the child welfare system for substance exposure (Feb 2008–April 2009), we used propensity score weighting to assess the association between out-of-home placement in infancy and measures of child attachment, behaviors, and social and cognitive development at 18 and 36 months. Our results indicate out-of-home placement for substance-exposed infants may increase risk of negative developmental outcomes compared to keeping infants in their homes, and suggest social workers and practitioners should be cognizant of alternatives to out-of-home placement when evaluating cases of infant substance exposure. Our results also suggest policies that structure decision-making regarding testing and placement may ultimately help improve child outcomes.